2006
DOI: 10.1007/s00192-005-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful voiding immediately after outpatient mid-urethral sling

Abstract: We set out to identify predictors of successful voiding immediately after outpatient mid-urethral sling. The charts of 126 patients who underwent an outpatient mid-urethral sling procedure were identified. Using discharge without a urinary catheter as the dependent variable, logistic regression analysis modeled the relationship of independent variables including demographic, preoperative urodynamic, and perioperative variables. Sixty-one percent of the patients passed their immediate postoperative voiding tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…Sokol et al (10) found that older age, low body mass index (BMI) and postoperative urinary tract infections (UTI) were independently associated with prolonged time to adequate voiding; however, in this study, a previous history of incontinence surgery was the only independent variable predictive of urinary retention. Barron et al (11) showed that parity over two and preoperative anxiety were independently associated with successful immediate voiding trial after a TVT procedure in their retrospective review of 126 patients. Barber et al (12) have found that poor preoperative detrusor function may have a role as well.…”
Section: Demographics and Other Associated Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sokol et al (10) found that older age, low body mass index (BMI) and postoperative urinary tract infections (UTI) were independently associated with prolonged time to adequate voiding; however, in this study, a previous history of incontinence surgery was the only independent variable predictive of urinary retention. Barron et al (11) showed that parity over two and preoperative anxiety were independently associated with successful immediate voiding trial after a TVT procedure in their retrospective review of 126 patients. Barber et al (12) have found that poor preoperative detrusor function may have a role as well.…”
Section: Demographics and Other Associated Factorsmentioning
confidence: 99%
“…In contrast, Minassian et al (19) retrospectively analyzed 138 patients who underwent antiincontinence surgery, including TVT, Burch or pubovaginal slings and found that patients with early postoperative VD (defined as a residual of >200 ml at discharge) had lower preoperative PVRs than those who did not (50 vs. 75 ml). Barron et al (20) reported that a Valsalva leak point pressure of more than 60 cm H 2 O and a maximum urethral closure pressure of more than 20 cm H 2 O were associated with a successful immediate voiding trial. Despite the aforementioned studies, numerous other studies have shown no association between postoperative VD and the parameters such as preoperative peak flow rate, preoperative PVR, Valsalva leak point pressureor severe intrinsic sphincter deficiency (15,18,(20)(21)(22)(23)(24).…”
Section: Urodynamic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Uroflow rates, postvoid residual volume, the presence of detrusor contraction at time of preoperative voiding study, the need for suprapubic catheter at time of discharge, and total number of days of catheterization have been associated with need to catheterize postoperatively [11][12][13][14][15][16][17][18][19]. Given this variation in reported associated variables, challenges exist when attempting to adequately counsel individual women regarding their likelihood of voiding success after USI surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Given this variation in reported associated variables, challenges exist when attempting to adequately counsel individual women regarding their likelihood of voiding success after USI surgery. These challenges are greater still when attempting to predict successful voiding before hospital discharge with only one out-patient trial [14] and one in-patient [16] trial currently reported in the literature.…”
Section: Introductionmentioning
confidence: 99%